A Generalized Demodicosis and Malasseziosis in a Pug Mix Dog - Ahlia Ummul Maslakah; Shelly Kusumarini (Universitas Airlangga, 2023)
A 12-year-old female pug mix dog presented a skin problem with itching, and alopecia in the neck, facial, and extremity areas. Findings of scales, hyperpigmentation, and erythema are present almost throughout the body, along with crusts on the cranial and caudal extremities and a foul body odor. Wood's lamp examination revealed a yellowish-green fluorescence in the ear and ventral areas of the body. The skin tape examination revealed an infestation of Demodex sp. mites accompanied by Malassezia sp. hematological analysis indicated that the dog presented anemia. The dog was diagnosed with demodicosis with a secondary infection of Malassezia sp. The therapy provided consisted of antiparasitic drugs such as imidacloprid and moxidectin (Advocate®); the long-acting antibiotic enrofloxacin was administered at a dose of 200 mg intramuscularly, along with the oral antibiotic amoxicillin and clavulanic acid at a dose of 31.25mg/kg BW every 12 hours. Additionally, oral antifungal medication ketoconazole was given at 25mg/kg BW every 12 hours, along with ketoconazole cream. Oral antihistamine mebhydroline napsylate was administered at 25mg/kg BW every 12 hours. Furthermore, multivitamins and hair vitamins were given at a dose of 2 ml once every 24 hours. After seven days of treatment, an evaluation was conducted, and it was observed that the dog's condition had improved, indicated by a reduction in the intensity of scratching.